2015
DOI: 10.1007/s00167-015-3704-7
|View full text |Cite
|
Sign up to set email alerts
|

The Bristow–Latarjet procedure, a historical note on a technique in comeback

Abstract: The Bristow-Latarjet procedure is a well-known surgical technique designed to treat shoulder instability. In this procedure, the coracoid process is transferred to the glenoid rim, to serve as augmentation of an associated bony defect. Because long-term results following a soft tissue procedure (Bankart repair) reveal that up to 21 and 33 % of the patients might experience recurrent instability and with the advent of the arthroscopic coracoid transfer, there is renewed interest in this procedure to treat shoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 35 publications
2
29
0
Order By: Relevance
“…The Latarjet technique has proven over the years to be a very effective and reliable procedure for the surgical treatment of anterior instability of the shoulder, especially in cases of glenoid bone loss, bipolar (humeral head and anterior glenoid) bone defects, and revision of surgical failures. 1 2 3 4 Also, the introduction of subscapularis muscle split, described by Patte, improved the results concerning recovery of external rotation. 5 In 2007, Lafosse et al described the arthroscopic Latarjet procedure (arthro-Latarjet) as an alternative to traditional open surgical technique with encouraging short-term results.…”
Section: Introductionmentioning
confidence: 99%
“…The Latarjet technique has proven over the years to be a very effective and reliable procedure for the surgical treatment of anterior instability of the shoulder, especially in cases of glenoid bone loss, bipolar (humeral head and anterior glenoid) bone defects, and revision of surgical failures. 1 2 3 4 Also, the introduction of subscapularis muscle split, described by Patte, improved the results concerning recovery of external rotation. 5 In 2007, Lafosse et al described the arthroscopic Latarjet procedure (arthro-Latarjet) as an alternative to traditional open surgical technique with encouraging short-term results.…”
Section: Introductionmentioning
confidence: 99%
“…Any glenoid bone lesion is an important risk factor for recurrence of glenohumeral dislocations, and isolated capsulolabral repair has higher recurrence rates than bone transfer surgeries in these patients; the larger the glenoid bone defect, the higher the risk. 5 , 6 , 7 , 8 , 19 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 …”
Section: Discussionmentioning
confidence: 99%
“…Then, in addition to labrum repair, they should consider the options of anterior glenoid reconstruction by means of coracoid transfer (i.e. the Bristow and Latarjet procedures) 31 or iliac bone grafting 32 as well as humeral head reconstruction using the remplissage procedure 33 or by transplantation. 34 The number of complications that patients experience could be used in evaluating the safety of a method.…”
Section: Discussionmentioning
confidence: 99%
“…Freedman et al 3 reported that there were no significant 2 Coracoid process transfers like the Bristow and Latarjet procedures are recommended for patients at high risk for recurrent instability and lead to favorable outcomes in the short term. 31 Practitioners should still be cautious regarding the long-term outcomes, because these require performing nonanatomical reconstruction procedures on young patients. Regardless of which procedure is performed, the treatment should follow the guidelines advocated by Rowe: anatomic dissection at the time of surgery, identification and repair of the lesions responsible for the instability, returning tissues to their anatomic locations, and early postoperative ROM.…”
Section: Discussionmentioning
confidence: 99%